RELEVANSI PEMIKIRAN PENDIDIKAN IBNU SINA PADA PENDIDIKAN MASA KINI - Rahman, Muhammad Irfandi; Shofiyah, Nida (Universitas Pendidikan Indonesia, 2019)
Abstract. This study discusses the thoughts of Ibn Sina in the field of education and its relevance in Islamic education today. This research is a library research with documentation study data collection methods and content analysis data analysis methods. The analytical method used in this study is qualitative with in-depth analysis techniques whose results are displayed in the form of descriptions. The results of this study include: (1) The main objective of education in Ibn Sina’s view is the achievement of insan kamil status through moral guidance and the provision of competencies needed by the community. Ibnu Sina classifies the curriculum based on the age level of students. There are several learning methods in the concept of Ibn Sina’s education, including the talqin, demonstration, exemplary and habituation methods, discussions, internships, assignments, tarbib, and targhib. Educators in Ibn Sina’s view must have noble character, have a strong personality, have good words, and have a sincere heart as a role model figure; (2) Ibn Sina’s thought of education is relevant to Islamic education on the aspect of objectives, aspects of curriculum, aspects of method, and aspects of teacher. Abstrak. Penelitian ini membahas pada pemikiran Ibnu Sina dalam bidang pendidikan dan relevansinya dalam pendidikan Islam pada masa kini. Penelitian ini merupakan penelitian kepustakaaan dengan metode pengumpulan data studi dokumentasi serta metode analisis data analisis isi. Metode analisis yang digunakan dalam penelitian ini adalah kualitatif dengan teknik analisis mendalam yang hasilnya ditampilkan dalam bentuk deskripsi. Hasil penelitian ini antara lain: (1) Tujuan utama pendidikan dalam pandangan Ibnu Sina adalah tercapainya insan kamil melalui pembinaan akhlak serta pembekalan kompetensi yang dibutuhkan masyarakat. Ibnu Sina mengklasifikasikan kurikulum berdasarkan jenjang usia peserta didik. Terdapat beberapa metode pembelajaran dalam konsep pendidikan Ibnu Sina, di antaranya metode talqin, demonstrasi, keteladanan dan pembiasaan, diskusi, magang, penugasan, tarhib, dan targhib. Pendidik dalam pandangan Ibnu Sina haruslah memiliki akhlak yang mulia, memiliki kepribadian yang tangguh, bertutur kata yang baik, serta memiliki hati yang tulus sebagai sosok panutan; (2) Pemikiran pendidikan Ibnu Sina tersebut relevan dengan pendidikan Islam pada aspek tujuan, aspek kurikulum, aspek metode, dan apsek pendidik.